Defining Immersive Learning - Phillip Motley; Beth Archer-Kuhn; Catharine Dishke Hondzel; Jennifer Dobbs-Oates; Michelle Eady; Janel Seeley; Rosemary Tyrrell (Teaching & Learning Inquiry: The ISSOTL Journal, 2024)
Immersive learning practices (ILPs) in higher education are multidisciplinary in nature and varied in levels of integration into the student learning process. They appear in a variety of higher education programs such as teacher education, social work, law, and health sciences, and in practices such as service-learning, study away, internships, and foreign-language instruction. Based on observations of teaching and data from an open-ended survey and semi-structured interviews with post-secondary educators from three different countries, this study theorizes that immersive learning practices are composed of six distinct underlying theoretical components that work in combination. These six components can be used to describe, define, compare, and design different types of structured ILPs. This study suggests that ILPs are pedagogically distinct from other forms of engaged and experiential learning.